A road map to change: application of a comprehensive change management model to guide and inspire fishers to reduce bycatch. (21st June 2022) - Eayrs, Stephen
Abstract: Two bycatch reduction initiatives in Australia's Northern Prawn Fishery were evaluated through the lens of a comprehensive change management model. This model combines the constructs of change Type, Readiness, Process, Inertia, and Time, and was developed because gear researchers have a poor record facilitating the voluntary uptake of proven fishing gear, including bycatch reduction devices. This evaluation identified where efforts by gear researchers to facilitate change in this fishery did and did not achieve desired outcomes. It identified differences in change type, precursors to change, and readiness of fishers to change, although extension activities were similar for both initiatives. No attempts were made to influence their affective readiness to change. During the second initiative, the process of overcoming inertia was influenced by a well-respected industry body. With a clear vision and improved fisher readiness to change, achievement of desired outcomes was relatively straightforward and less controversial. The proactive application of this model in the fishing industry awaits. However, this evaluation implies it is a useful road map to guide and inspire change in this industry. In the future, efforts to realize change must include consideration of affective change readiness, establishment of a guiding coalition, and promulgation of a clear vision.